PERFORMA MESIN MOTOR BERBAHAN BAKAR ETANOL DENGAN PERUBAHAN KAPASITAS MESIN DAN 2 BUSI - Farid Majedi; Fredy Susanto (Jurnal Poli-Teknologi, 2018)
ABSTRACTPetroleum reserves are running low. To solve this problem by optimizing the use of petroleum products, used ethanol for gasoline replacement. The motor is modified so that the use of ethanol as a substitute for gasoline can be done. This study aims to see the engine performance with changes in engine capacity and the use of 2 spark plugs. This research method is to modify engine capacity from 113,7 cc to 100,45 cc and use 2 spark plugs. Performance testing of 95% ethanol fuel modification engine with Dynometer test machine, to determine power, torque and fuel consumption. Performance modification of gasoline engine and 1 spark plug is also tested, then compared. The results showed that the power in the engine capacity of 100.45 cc with ethanol fuel 95% smaller 7.3% compared to the power on the engine capacity of 100.45 cc with fuel pertalite. Torque on the engine capacity of 100.45 cc with ethanol fuel 95% smaller 7.5% compared to torque on the engine capacity of 100.45 cc with fuel pertalite. Fuel consumption on 100.45 cc engine fueled ethanol 95% larger 43.6% compared to fuel consumption in the engine capacity of 100.45 cc with fuel pertalite.Keywords : Engine capacity, 2 spark plugs, ethanol, Power, torque.ABSTRAKCadangan minyak bumi mulai menipis. Untuk mengatasi masalah ini dengan mengoptimalkan penggunaan produk minyak bumi, digunakan etanol untuk pengganti bensin. Motor dimodifikasi agar penggunaan etanol sebagai pengganti bensin dapat dilakukan. Penelitian ini bertujuan untuk melihat performa mesin dengan perubahan kapasitas mesin dan penggunaan 2 busi. Metode penelitian ini adalah memodifikasi kapasitas mesin dari 113,7 cc menjadi 100,45 cc dan menggunakan 2 busi. Pengujian kinerja mesin modifikasi bahan bakar etanol 95% dengan mesin uji Dynometer, untuk menentukan daya, torsi dan konsumsi bahan bakar. Performa modifikasi mesin bahan bakar bensin dan 1 busi juga diuji, kemudian dibandingkan. Hasil penelitian menunjukkan Daya pada mesin berkapasitas 100,45 cc dengan bahan bakar etanol 95% lebih kecil 7,3% dibandingkan pada daya pada mesin berkapasitas 100,45 cc dengan bahan bakar pertalite. Torsi pada mesin berkapasitas 100,45 cc dengan bahan bakar etanol 95% lebih kecil 7,5% dibandingkan torsi pada mesin berkapasitas 100,45 cc dengan bahan bakar pertalite. Konsumsi bahan bakar pada mesin berkapasitas 100,45 cc berbahan bakar etanol 95% lebih besar 43,6% dibandingkan konsumsi bahan bakar pada mesin berkapasitas 100,45 cc dengan bahan bakar pertalite.Kata kunci : Kapasitas mesin, 2 busi, etanol, Daya, torsi.